Glaube in der multireligiösen Gesellschaft: Zur Bildungskompetenz evangelischen Glaubensverständnisses - Danz, Christian (HTS teologiese studies, 2007)
An evangelical understanding of religion: The establishment of sensible communication within religious and cultural pluralities. The article argues that when different religions and cultures live together in modern societies, it will result in a great deal of conflict. It is also true of Systematic Theology driven by confessions if contact among the religious worlds of modern people is not to be lost or proof of the theoretical religious competence thereof is not to be compromised. This article discusses various theological models to include the reality of the pluralism of societies and attempts to take the existing discussions of the theology of religion further by promoting a certain model that possesses the basic grounds of Reformed Christianity. The thesis of the article reveals that with an evangelical understanding of religion, a certain encounter among religious and cultural differences can be reflected. An obvious religious understanding should not only be in mind, but also the establishment of sensible communication within religious and cultural pluralities.